ANALISIS KINERJA KARYAWAN MEMPERHATIKAN FAKTOR KEPEMIMPINAN, BUDAYA ORGANISASI DAN LINGKUNGAN KERJA (STUDI PADA LEMBAGA RESTORATIVE JUSTICE WORKING GROUP ACEH) - Inayati, Wirda; Syahriani, Endang; Mirza, Mirza (IndOmera, 2024)
The research aims to descriptively analyze and verify employee performance by considering the direct and indirect impacts of leadership factors, organizational culture or work environment. Study of 47 employees of the Aceh Restorative Justice Working Group (RJWG). Analysis uses quantitative methods and analysis techniques use path analysis models. The results of the research found several conclusions, namely (1) employee performance is influenced both directly and indirectly by hypothesized factors, namely leadership factors of 38.42%, work culture factors in institutions of 41.89% and the contribution of the work environment to performance. employee. 53. .95%, (2) Simultaneously the three factors, namely leadership, organizational culture and work environment, influence the performance of RJWG Aceh employees by 56%.